Development and diapause induction of the Indian meal moth, Plodia interpunctella (Hübner) (Lepidoptera: Pyralidae) at different photoperiods - Md. Mahbub Hasan (Nature Portfolio, 2020)
Abstract Diapause concerns the fascinating phenomenon in the biology of insect development which allows better understanding the local adaptation and phenotypic plasticity to seasonal variations in environment. There is lot of reasons to carry out the research on diapause both for fundamental and applied sciences. Photoperiod is one of the main environmental cues followed by insects to predict the forthcoming seasonal changes and to adapt these changes in their life-history traits. Thus, the effect of different photoperiod regimes on development and diapause induction of larvae of the Indian meal moth Plodia interpunctella (Hübner) was evaluated at a constant temperature of 17 °C. Development was significantly faster at a photoperiod of 12:12 light:darkness (L:D) than at 8:16, 10:14, 14:10 and 16:8 L:D. A photoperiod of 12:12 (L:D) induced most larvae (≥ 71%) to enter diapause, while this percentage was slightly lower (60%) at both shorter(8 h) and longer (16 h) day lengths (50%). The different photoperiod regimes did not affect the percentage of adult emergence. Fat and protein composition of the diapausing larvae differed significantly among treatments as well as between diapausing and non-diapausing larvae. Larvae developing from 8:16 (L:D) contained the maximum amount of protein (36.8%) compared to other regimes, while the minimum amount (21.0%) was noted in larvae that developed at 16:8 (L:D). Six types of fatty acids were detected in the larvae: myristic acid (methyl tetradecenoate), palmitoleic acid (9-hexadecenoic acid, methyl ester), palmitic acid (hexadecenoic acid, methyl ester), linoleic acid (9, 12-Octadecadienoic acid (Z, Z), methyl ester), oleic acid [9-octadecenoic acid, methyl ester (E)] and stearic acid (octadecanoic acid, methyl ester). The results also reveal that the percent of fatty acids detected in the diapausing larvae varies significantly and the same trends imply in the interaction of fatty acid and photoperiod regimes. Moreover, three quarters of the total variance was accounted for by the Principal Component Analysis (PCA) of the fatty acids. Different proportions of fatty acids were noted among treatments, suggesting that photoperiod influences a number of key biological traits in P. interpunctella, much more than the percentage of the diapausing larvae per se.